Plan de negocios para la producción y comercialización de cortinas y persianas para venta por catálogo en la ciudad de Quito - Soria Moya, Santiago Javier (2012)
This business plan aims at creating Lizan Desing, a company that will dedicate to the production and commercialization of curtains and blinds for catalogue sales in the city of Quito. One of the incentives for the creation of the company is that the construction sector is growing and the curtains like decorative complementary product is a clear need for the persons who acquire a department, house or new office. Inside the analysis of the industry the possible scenes of the business were analyzed; the risks and the opportunities from which it can benefit to determine the feasibility of the same one. To determine the target market there was realized a market research that included the offer, the demand, tastes, and preferences of the consumer and the strategies to commercialize it were done analyzing the experiences of the experts in the branch. The marketing plan describes the strategies to be implemented to position the company among the top 5 in Quito´s market, and achieve a 5% stake in the local market in the first year of operations. The company reaches its point of balance with the sale of 4.830 m2 of curtains and blinds, evidenced in Chapter IX. The point of balance calculation was made considering that the variety of models on the market for curtains and blinds causes a variation in production costs according to each model, thus determining the point of balance is considered fixed costs and variable costs versus the square footage needed to sell at an average price. The management plan identified the organizational structure, profiles of jobs, and the staff that the company will count is as follows: administrative, sales and operational; will also have external advice of consultants and lawyers, who constitute an advisory body to support management for the proper manage of business operations and legal procedures. The remunerations that the collaborators will perceive take all the benefits of law as an affiliation to the social insurance, reserve funds, vacations and bonds for labor performance. The financial plan establishes an initial investment of approximately $ 117.718 and can be leveraged by a loan from the Corporación Financiera Nacional – CFN at an interest of 9,53%, according to the capital structure described in Chapter X. There is demonstrated that the business plan is profitable and has a considerable return for the shareholders since dividends will be distributed from the first year of operations. The financial study shows that the business plan is profitable and has a significant return to shareholders as dividends will be declared from the first year of operations. The following summarizes the financial results of the project with three scenarios.